Peculiarities of the morphology of liver biopsy samples of donors above 60 years of age - I. M. Iljinsky; N. P. Mozheyko; D. V. Voronov; M. G. Minina; O. M. Tsirulnikova (Вестник трансплантологии и искусственных органов, 2020)
Objective: to study the differences in the frequency of pathological processes in liver biopsy samples of donors older than 60 years (group 1) and donors currently recognized as “standard” by age – 60 years and younger (group 2). Material and methods. Of the total pool of 300 consecutive donors with brain death, there were 28 (9.3%) donors over 60 years old (61 to 73 years old; 19 men and 9 women). Results. The frequency of pathology is independent of gender in both groups (p > 0.05). In elderly donors, compared with “standard” donors, mild (p < 0.05) and significantly more often severe (p < 0.05) albuminous degeneration are significantly less frequent, and there is only a tendency (p > 0.05) to more frequent mild hepatic steatosis. Dystrophic processes are the result of more severe ischemic injury to the liver of elderly donors. Ischemic liver injury determines the risk of more frequent biliary complications, which require careful monitoring and maintenance at an optimal level of hemodynamics for donors in the intensive care unit. Based on other morphological parameters, the liver of donors above 60 years of age does not significantly differ (p > 0.05) from the liver of donors 60 years and younger. Conclusion. To expand the donor pool, age restrictions should be removed when selecting a liver for transplantation, thereby maximizing the use of donor potential.